(untitled) (Bangladesh Journal of Child Health, 2025)
Empyema thoracis, an effect of pneumonia characterized by the accumulation of pus in the space between the lungs and the chest wall, poses a considerable difficulty in the field of pediatric medicine. This case report examines the progression of a child with empyema thoracis, focusing on the diagnostic and treatment methods followed. The patient is a 10-year-old boy who has a history of right-sided chest pain, difficult breathing with sputum and also high fever. Diagnostic imaging indicated the existence of pleural effusion, and thoracentesis retrieved purulent fluid, confirming the diagnosis. The management of the ailment required a holistic strategy that involved the administration of antibiotics, drainage of the chest tube, and provision of supportive care. The patient exhibited a gradual enhancement in response to the treatment, underscoring the significance of swiftly detecting and vigorously addressing empyema thoracis in children to mitigate adverse health consequences and mortality. The aforementioned example demonstrates the significance of being vigilant in pediatric patients with pneumonia, particularly those with persistent or worsening symptoms, to prevent complications such as empyema thoracis. BANGLADESH J CHILD HEALTH 2023; VOL 47 (3) : 178-181